Ant-colony based optimal MC-CDMA multiuser detector - Hijazi, S. L.; Best, A. J.; Natarajan, Bala; Das, Sanjoy (Institute of Electrical and Electronics Engineers, 2005)
In this paper, we present a novel multiuser detection (MUD) technique based on ant colony optimization (ACO), for synchronous multi-carrier code division multiple access (MC-CDMA) systems. ACO algorithms are based on the cooperative foraging strategy of real ants. While an optimal MUD design using an exhaustive search method is prohibitively complex, we show that the ACO based MUD converges to the optimal MUD BER performance in relatively few iterations providing 98% saving in computational complexity.
Keywords: Code division multiple access; Error statistics; Multiuser detection; Optimisation; Ant colony; MUD technique